The conservative treatment of ligamentogenic lumbopelvic pain - Istomin, Andrii; Kalyuzhka, Аlina; Istomin, Dmytro; Kyryllov, Viktor; Zhuravska, Iuliia; Dorohan, Kseniia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
An increased density of ligaments in the lumbopelvic region, that is typical for ligamentopathy, causes redistribution of the stressstrain state of structures in the biomechanical system «lumbar spine – sacrum – sacroiliac joint – pelvis», thereby provoking development of degenerative-dystrophic changes. Proceeding from the above, the concept of conservative treatment for ligamentogenic lumbopelvic pain (LLPP) should provide restoration of the natural density of the ligament and use of structuremodifying medicines. Objective: to develop a biomechanically and pathogenetically based technology for the conservative treatment of LLPP and assess of the efficacy of its use. Methods: 45 patients with LLPP were divided into three groups: I — extracorporeal shock-wave therapy, II — dietary supplement «Protecta», III — integrated treatment with dietary supplement «Protecta» in combination with shock-wave therapy. The patients’ condition was assessed before the treatment, after 1 and 3 months following its finishing. Results: reduction of the pain and functional limitations was registered in patients from all the groups. Nevertheless the pain, stiffness and functional insufficiency decreased most significantly in cases from group III. Following 1 and 3 months after the end of their treatment course, these patients’ blood serum revealed lower values of destruction in their cartilaginous and osseous tissues as well as a reduced activity of marker enzymes. Biochemical marker values after 1 month following the end of their treatment course in patients from groups I and III were better versus group II, but after 3 months the dynamics of the examined indices were more expressed in groups II and III. Conclusion: the developed technology for conservative treatment of LLPP with use of extracorporeal shock-wave therapy and dietary supplement «Protecta» is effective, as it is confirmed by results of clinical and biochemical studies.